2022
DOI: 10.1002/wnan.1787
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectricity‐coupling patches for repairing impaired myocardium

Abstract: Cardiac abnormalities, which account for extensive burdens on public health and economy, drive necessary attempts to revolutionize the traditional therapeutic system. Advances in cardiac tissue engineering have expanded a highly efficacious platform to address cardiovascular events, especially cardiac infarction. Current efforts to overcome biocompatible limitations highlight the constructs of a conductive cardiac patch to accelerate the industrial and clinical landscape that is amenable for patient-accurate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that both non‐conductive and conductive (salts of) polyaniline (emeraldine) promote the adhesion and proliferation of H9c2 cardiac myoblasts in a manner comparable to that of the tissue culture plate (TCP). Such results underline that after a brief period of deviation from their normal morphology, H9c2 returned to their normal morphology, indicating that conductive emeraldine can be considered an electroactive scaffold for cardiac (and presumably neuronal) tissue engineering 10,24 . Similar to well‐known growth signaling agents such as growth factors and adhesive proteins, it is becoming increasingly evident that electrical signaling plays a role in the adhesion and normal function of particular cell species, such as cardiac cells.…”
Section: Conductive Polymers In Cardiac Tissue Engineeringmentioning
confidence: 69%
See 4 more Smart Citations
“…It has been demonstrated that both non‐conductive and conductive (salts of) polyaniline (emeraldine) promote the adhesion and proliferation of H9c2 cardiac myoblasts in a manner comparable to that of the tissue culture plate (TCP). Such results underline that after a brief period of deviation from their normal morphology, H9c2 returned to their normal morphology, indicating that conductive emeraldine can be considered an electroactive scaffold for cardiac (and presumably neuronal) tissue engineering 10,24 . Similar to well‐known growth signaling agents such as growth factors and adhesive proteins, it is becoming increasingly evident that electrical signaling plays a role in the adhesion and normal function of particular cell species, such as cardiac cells.…”
Section: Conductive Polymers In Cardiac Tissue Engineeringmentioning
confidence: 69%
“…Such results underline that after a brief period of deviation from their normal morphology, H9c2 returned to their normal morphology, indicating that conductive emeraldine can be considered an electroactive scaffold for cardiac (and presumably neuronal) tissue engineering. 10,24 Similar to well-known growth signaling agents such as growth factors and adhesive proteins, it is becoming increasingly evident that electrical signaling plays a role in the adhesion and normal function of particular cell species, such as cardiac cells. It is hypothesized that this impact is the result of electrical, mechanical, and topographical cues supplied by CPs to cells, specifically stem cells.…”
Section: Conductive Polymers In Cardiac Tissue Engineering 21 | Intri...mentioning
confidence: 99%
See 3 more Smart Citations